Behavior of Natural Estrogens in Activated Sludge: Biodegradation in Semicontinuous Reactor under Aerobic, Anaerobic and Sequential Anaerobic/Aerobic Conditions - Desmiarti, Reni; Li, Fusheng (Journal of Engineering and Technological Sciences, 2013)
The behavior of natural estrogens was examined by separately spiking 17Î²-estradiol (E2) and estrone (E1) into semicontinuous activated sludge reactors operated under aerobic, anaerobic and sequential anaerobic/aerobic conditions. Under aerobic and anaerobic conditions, E1 was formed from E2. The cactivated sludge; biodegradation; estrogens; estradiol; estroneonversion of E1 to E2 was did not occur under aerobic conditions. The maximum conversion of E2 to E1 was higher than the maximum conversion of E1 to E2. Overall, the degradation rate of E2 (kE2) was much faster than that of E1 (kE1). The findings suggest that E1 is probably more persistent than E2 in effluent of sewage treatment plants.